Pengembangan Kompetensi Bahasa Inggris Anak melalui Microteaching Berbasis CLIL - Wahab, Aulia Dwi Amalina (INCARE, International Journal of Educational Resources, 2025)
This study aims to examine the application of microteaching based on the Content and Language Integrated Learning (CLIL) approach in improving the competence of prospective Early Childhood Education (PAUD) students in teaching English. The CLIL approach, which integrates foreign language learning with thematic content, is considered effective for implementation in early childhood education. Meanwhile, microteaching is a training strategy that allows students to practice pedagogical skills on a small and structured scale. The method used is a qualitative descriptive case study with 25 students from Mataram University who were randomly selected from 112 fourth-semester students as participants. Data were collected through structured observations during microteaching sessions and analyzed descriptively and quantitatively using percentages. The results showed that student competence in implementing the CLIL approach was classified as good, with the highest achievements in the cultural aspects (90%) and content (87%), especially in the use of interesting and contextual learning media. However, the communication and evaluation aspects of learning still need improvement, especially in encouraging children to interact actively in English and in designing objectives and assessments that are appropriate for children's development. These findings indicate that integrating CLIL into microteaching can equip students with practical and reflective skills in teaching English to early childhood, while also supporting their professional development as adaptive and competent prospective early childhood teachers.